The nucleation of Mo-rich Laves phase particles adjacent to M23C6 micrograin boundary carbides in 12% Cr tempered martensite ferritic steels. (15th May 2015) - Isik, M.I.; Kostka, A.; Yardley, V.A.; Pradeep, K.G.; Duarte, M.J.; Choi, P.P.; Raabe, D.; Eggeler, G.
Abstract: We study the nucleation of Mo-rich Laves phase particles during aging and creep of 12 wt.% Cr tempered martensite ferritic steels (TMFS). Recently, in Isik et al. (2014) we reported that Laves phase particles tend to form at micrograin boundaries of TMFSs after Mo and Si had segregated from the ferritic matrix to these internal interfaces. In the present work, we employ transmission electron microscopy (TEM) and atom probe tomography (APT) to study the formation of Laves phase particles. We investigate the preference of Laves phase particles to nucleate next to M23 C6 micrograin boundary carbides. Our results suggest that this joint precipitation effect is due to the combined segregation of Mo and Si from the matrix to the micrograin boundaries and Si and P enrichment around the growing carbides.